2022
DOI: 10.1007/s40593-022-00309-y
|View full text |Cite
|
Sign up to set email alerts
|

Three Algorithms for Grouping Students: A Bridge Between Personalized Tutoring System Data and Classroom Pedagogy

Abstract: Computer-assisted instructional programs such as intelligent tutoring systems are often used to support blended learning practices in K-12 education, as they aim to meet individual student needs with personalized instruction. While these systems have been shown to be effective under certain conditions, they can be difficult to integrate into pedagogical practices. In this paper, we introduce three group formation algorithms that leverage learning data from the adaptive intelligent tutoring system ALEKS to supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…These platforms analyze students' responses to questions and adjust the difficulty level and content of subsequent questions based on their performance, ensuring that each student receives personalized feedback and support (Hashim, et. al., 2022, Lechuga & Doroudi, 2023, Moleka, 2023.…”
Section: Ai-driven Assessment and Feedbackmentioning
confidence: 99%
“…These platforms analyze students' responses to questions and adjust the difficulty level and content of subsequent questions based on their performance, ensuring that each student receives personalized feedback and support (Hashim, et. al., 2022, Lechuga & Doroudi, 2023, Moleka, 2023.…”
Section: Ai-driven Assessment and Feedbackmentioning
confidence: 99%
“…In the other seven studies (23.3%), the use of AI technology was found in both the online and offline classroom environments. For example, Lechuga and Doroudi (2022)…”
Section: Research Trends Related To Ai In Blended Learningmentioning
confidence: 99%
“…We believe that AI can help instructors control students' autonomy. In the literature, we found that AI was a direct mediator to provide personalized instruction and scaffolding for individual learners (Lechuga & Doroudi, 2022;Phillips et al, 2020). More specifically, an online learning system powered by AI technology assigned repetitive practice (Lu et al, 2021), provided real-time alerts and feedback to prompt students to participate in daily or weekly discussions (Jovanović et al, 2017;Liao & Wu, 2022), and increased the probability of students achieving learning mastery (Phillips et al, 2020).…”
Section: Contributions Of Ai In Blended Learningmentioning
confidence: 99%
“…The use of artificial intelligence in education is becoming widespread in different parts of the world under different platforms. For example, some schools use ALEKS (Assessment and Learning in Knowledge Spaces), which has features such as tracking student homework, selfdirected learning, and assessment, and meets a critical need, especially in algebra teaching, as well as in mathematics, chemistry, statistics (Lechuga & Doroudi, 2022;Matayoshi & Uzun, 2022;Phillips et al, 2020). After quickly and accurately determining each student's precise knowledge of a topic, ALEKS helps the student to work on the topics they are ready to learn (ALEKS, 2023).…”
Section: Artificial Intelligence In Educationmentioning
confidence: 99%